Performance and clinical implications of non-invasive prenatal testing for rare chromosomal abnormalities: a retrospective study of 94,125 cases - Qi, Haimei; Chen, Haijun; Zhang, Zhuling; Gan, Jinhui; Liu, Huifeng; Yuan, Xianping; Luo, Fuyu; Chen, Junkun; Shen, Shichun (Frontiers in Molecular Biosciences, 2025)
BackgroundNon-invasive prenatal testing (NIPT) has demonstrated robust performance in detecting common trisomies and copy number variations. However, its clinical utility for rare chromosomal abnormalities (RCAs) remains controversial due to low positive predictive value (PPV).MethodsThis study retrospectively analyzed the data of 94,125 cases that underwent NIPT at Ganzhou Maternal and Child Health Hospital in China. This dataset was used to evaluate NIPT performance in RCAs detection and track pregnancy outcomes of positive cases.ResultsIn the cohort of 94,125 pregnancies undergoing NIPT, 336 cases (0.36%) were found to carry RCAs. Among them, 102 cases underwent validation through karyotyping and/or chromosome microarray analysis. Of the 102 validated cases, seven were true positives (PPV = 6.86%). Additionally, 3 cases exhibited uniparental disomy consistent with the NIPT-reported chromosomal anomalies. Of 268 singleton neonates, 68 (25.37%) were small-for-gestational-age.ConclusionThis study found that most NIPT-detected RCAs were associated with maternal age, while Trisomy seven occurred independently of maternal age. Concurrent use of karyotyping and chromosome microarray analysis, rather than karyotyping alone, mitigates culture-related bias and enhances the PPV. Both biological and methodological factors contribute to the low PPV of NIPT for RCAs. Despite a low PPV, pregnancies with NIPT-indicated RCAs showed elevated risks of fetal loss, small-for-gestational-age, and uniparental disomy, though not preterm birth. Thus, NIPT-detected RCAs retain clinical significance for risk stratification and pregnancy management.